HUMANITY AS A WORLDVIEW PRINCIPLE OF SOCIAL PROJECTING IN THE AGE OF MODERN GLOBAL CHALLENGES - Mokliak, Laryca (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The current situation that has developed in our country and the world in general has obviously aggravated the problem of reassessment and formation of a new model of ethical guidelines that would allow a person and society, in general, to find spiritual support for their modern existence. The aim and tasks of the study are to analyze and determine the factors and socio-cultural mechanisms that, in the modern aggressive reality created by war, contribute to the preservation, cultivation, and active manifestation of one of the fundamental principles of morality - humanity. Identification of the most relevant spiritual and moral forms of social ties through which humanity manifests itself in the human community and is able to be an effective cultural and civilizational means of uniting society in opposition to modern barbarism. From this angle, the ability and attitude of such a sphere of social management as social design, which defines its goal as the promotion of modernization and support in society both in the material and spiritual spheres, are investigated. The basis of the research methodology is the dialectical method, which is used at all levels of analysis of the phenomenon of humanity, and the contradictions of its manifestation in the modern civilizational crisis. Involvement of conceptual analysis allows the revealing of the essential characteristics of the category "humanity" in relation to the categories "social project", "responsibility", "solidarity", "tolerance", "charity". The interdisciplinary nature of the topic, and its value load necessarily required the use of the comparative method. The theoretical basis of the study was the works of domestic researchers in the field of philosophical anthropology, social philosophy, ethics, philosophy of culture, sociology, and psychology. Research results. Firstly, it is the fact that humanity is able to essentially reveal itself only beyond the boundaries of humanistic ideology, which is built on the principle of anthropocentrism. Humanity is not an affirmation of human nature in itself, contrary to everything else. Secondly, humanity as a measure of humanness presupposes human responsibility, the ability to limit oneself in one’s needs and interests when one meets the needs and interests of the common world of one’s existence. Humanity presupposes a person’s openness to the Other, being tolerant of the Other, perceiving and understanding, and respecting his life world. Discussion. The analysis carried out shows that in a society in which the basic institutions of management, analysis, and forecasting of social processes lay down moral and ethical parameters of humanity in their project activities, optimal solutions to social problems are guaranteed to be found, and they really contribute to the harmonization of social relations. The author notes that sociality does not contradict humanity. The etymology of this term translated from Latin means cohesion, community, connection, and not totality. The latter is possible precisely on the moral and value bases of humanity. Conclusions. Sociality is the semantic epicenter of society, a way of organizing individuals in society. Determining the prospects for the development of social relations is a necessary prerequisite for achieving a new qualitative state of social and other spheres of society’s life, in particular, the man himself - the basic value of any civilized society. The priority of this direction actualizes the task of scientifically based forecasting and implementation of practical social technologies and their practices. An important role in the activity of modern social spheres is played by such an innovation as social projecting. Social projecting, which has become widespread in modern Ukraine, is aimed at solving painful, urgent problems of social existence and covers not only issues on a national scale but also aimed at the level of the region, district, and social groups. But, without taking into account the value and moral imperative of human-sizedness (humanity), hoping for its successful implementation is futile.